Economic Analysis of Off-Grid Energy Projects: A FINPLAN Model Approach - Benneth C. Oyinna; Kenneth E. Okedu; Gauri Kalnoor; Leo Raju; V. B. Murali Krishna; Ilhami Colak (IEEE Access)
Off-grid energy projects particularly solar mini-grids, play a crucial role in electrifying remote areas with limited access to centralized grids. This paper presents an economic assessment of a 20.46kWp solar mini-grid project using the model for financial analysis of electric sector expansion plans (FINPLAN) model, a financial planning tool used in energy project financial evaluation. The study aims to analyse the financial viability, risks, and economic benefits of off-grid solar solutions. Key indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Break-even Point (BEP), and Exchange Risk and Debt Service Coverage Ratio (DSCR) are evaluated to determine the project viability and sustainability. The FINPLAN model approach allows detailed cash flow analysis and risk assessments under various scenarios of energy demand, capital expenditure, operational costs, and subsidy frameworks. The case study of a 20.46kWp Solar PV-Battery Energy Storage System (BESS) project highlights the impact of key financial parameters, such as interest rates and inflation, on project returns. The study reveals that an additional equity investment of $=\!\!\!\!\!\!{\text{N}}$ 189.06 million is needed for procurement in 2025 and early operational costs in 2026, with a positive Net Present Value of $=\!\!\!\!\!\!{\text{N}}$ 15497.33 and an equity Internal Rate of Return (IRR) of 27.66%. The financial ratios show a Working Capital Ratio (WCR) of 1.35-4.0, exchange risk of 0.1-15, break-even point value >0.8 between 2026 and 2036, and a Debt Service Coverage Ratio of 0.3-1.2 between 2026 and 2036. The Best-Case scenario results showed a more balanced case with no flow from the stand-by facility, a positive NPV of $=\!\!\!\!\!\!{\text{N}}$ 17,805.71, and an Equity IRR of 26.96%. The paper recommends the adoption of the FINPLAN tool for appraising off-grid energy projects and power infrastructure expansions.